The Best of Both Wolves - Spear, Terry (Naperville, Illinois : Sourcebooks Casablanca, 2022)
Earning a job with the Portland police department as a sketch artist, Sierra Redding gets a chance to get closer to handsome investigator Adam Holmes when one of her drawings leads him to a thief who is determined to make her life miserable.
Keywords: Werewolves -- Fiction; Shapeshifting -- Fiction; Police artists -- Fiction; Witnesses -- Fiction; Robbery -- Fiction; Portland (Or.) -- Fiction; Paranormal fiction; Novels; Romance fiction